A statistical approach to assess the schedule delays and risks in Indian construction industry. Issue 5 (2nd September 2020) - Muneeswaran, G.; Manoharan, P.; Awoyera, P. O.; Adesina, A.
Abstract: Construction projects are highly complex and dynamic in nature. However, its dynamicity subjects it to several delays and risks; before, during and after construction. Therefore, it is paramount to identify the possible sources of delays and risks so as to prioritize them. This study used a literature review and perception of construction professionals in the Indian construction industries to assess and prioritize delays and risks. Statistical analysis using relative importance index and fuzzy ranking was employed to identify, assess, and prioritize delays and risks in the Indian construction industry context. Inadequate schedule was found to be the most critical risk, which constitutes a long-term problem in any construction projects. New risks were identified in the tendering stage. It is anticipated that the result of this study would be a guidebook for all stakeholders in the construction industry to assess and prevent any possible delay and risk in their construction processes.